Accuracy of rapid point-of-care antigen-based diagnostics for SARS-CoV-2: an updated systematic review and meta-analysis with meta regression analyzing influencing factors [Research Data] - Brümmer, Lukas E.; Katzenschlager, Stephan; McGrath, Sean; Schmitz, Stephani; Gaeddert, Mary; Erdmann, Christian; Bota, Marc; Grilli, Maurizio; Larmann, Jan; Weigand, Markus A.; Pollock, Nira R.; Macé, Aurélien; et al. (Universität, 2022)
Background Comprehensive information about the accuracy of antigen rapid diagnostic tests (Ag-RDTs) for SARS-CoV-2 is essential to guide public hea...